Solid Waste Management Options for Maine: The Economics of Pay-by-the-bag Systems - Seguino, Stephanie; Criner, George; Suarez, Margarita (Maine Policy Review, 1995)
State and federal environmental mandates during the last three decades have changed the nature of the debate over solid waste disposal, but not the basic question: What do we do about the garbage we produce? Unlike years past, however, disposal options are now fewer and more costly. This has resulted in a shift in focus away from solutions that simply try to deal with the output of the disposal process—the trash—to those that focus on inputs—reducing the volume of materials going into the waste stream. Among the volume reduction strategies are recycling, which focuses on specific input materials, and volume-based fees, such as pay-by-the-bag (PB) solid waste disposal systems.
Keywords: Maine; solid waste management